Fragrance allergy: assessing the safety of washed fabrics - Basketter, David A.; Pons-Guiraud, Annick; Van Asten, Arian; Laverdet, Catherine; Marty, Jean-Paul; Martin, Ludovic; Berthod, Daniel; Siest, Sylvie; Giordano-Labadie, Françoise; Tennstedt, Dominique; Baeck, Marie; Vigan, Martine; et al. (Contact dermatitis, 2010)
Background: Previously, a quantitative risk assessment suggested there was no risk of induction of fragrance allergy from minor residues of fragrance chemicals on washed fabrics. Objective: To investigate whether there was any risk of the elicitation of contact allergy from fragrance chemical residues on fabric in individuals who were already sensitized. Methods: Thirty‐six subjects with a positive patch test to isoeugenol (n = 19) or hydroxyisohexyl 3‐cyclohexene carboxaldehyde (n = 17) were recruited. Dose–response and fabric patch tests were performed, respectively, with filter paper and a cotton sample loaded with fragrance in ethanol–diethylphthalate (DEP) and applied in a Finn Chamber® or a Hill Top Chamber®. Results: Only two subjects reacted to an isoeugenol patch test concentration of 0.01% (>20× the estimated likely skin exposure level), none reacted to lower concentrations. Of 36 subjects, 18 reacted to the fabric patch treated with ethanol–DEP vehicle alone and 20 to the fragrance‐chemical‐treated fabric patch. These were only minor non‐specific skin reactions. They were also quite evenly distributed between the two fragrance chemical allergic groups. Conclusions: On the basis of the examples studied, fragrance chemical residues present on fabric do not appear to present a risk of the elicitation of immediate or delayed allergic skin reactions on individuals already sensitized.